Complex karyotype in patients with mantle cell lymphoma predicts inferior survival and poor response to intensive induction therapy. Issue 11 (26th March 2018) - Greenwell, I. Brian; Staton, Ashley D.; Lee, Michael J.; Switchenko, Jeffrey M.; Saxe, Debra F.; Maly, Joseph J.; Blum, Kristie A.; Grover, Natalie S.; Mathews, Stephanie P.; Gordon, Max J.; Danilov, Alexey V.; Epperla, Narendranath; et al.
Abstract : BACKGROUND: Risk stratification of newly diagnosed patients with mantle cell lymphoma (MCL) primarily is based on the MCL International Prognostic Index (MIPI) and Ki‐67 proliferative index. Single‐center studies have reported inferior outcomes in patients with a complex karyotype (CK), but this remains an area of controversy. METHODS: The authors retrospectively reviewed 483 patients from 5 academic centers in the United States and described the effect of a CK on survival outcomes in individuals with MCL. RESULTS: A CK was found to be associated with inferior overall survival (OS) (4.5 vs 11.6 years; P <.01) and progression‐free survival (PFS) (1.9 vs 4.4 years; P <.01). In patients who underwent high‐intensity induction followed by autologous stem cell transplantation (ASCT) in first remission, a CK was associated with poor OS (5.1 vs 11.6 years; P = .04) and PFS (3.6 vs 7.8 years; P <.01). Among patients with a CK, high‐intensity induction had no effect on OS (4.5 vs 3.8 years; P = .77) nor PFS (2.3 vs 1.5 years; P = .46). Similarly, ASCT in first remission did not improve PFS (3.5 vs 1.2 years; P = .12) nor OS (5.1 vs 4.0 years; P = .27). On multivariable analyses with Ki‐67 and MIPI, only CK was found to be predictive of OS (hazard ratio [HR], 1.98; 95% confidence interval [95% CI], 1.12‐3.49 [ P = .02]), whereas both CK (HR, 1.91; 95% CI, 1.17‐3.12 [ P = .01]) and Ki‐67 >30% (HR, 1.86; 95% CI, 1.06‐3.28 [ P = .03]) were associated with inferior PFS. Multivariable analysis did not identify any specific cytogenetic abnormalities associated with inferior survival. CONCLUSIONS: CK appears to be independently associated with inferior outcomes in patients with MCL regardless of the intensity of induction therapy and receipt of ASCT. Cytogenetics should be incorporated into the workup of a new diagnosis of MCL and novel therapeutic approaches should be investigated for patients with CK. Cancer 2018;124:2306‐15 . © 2018 American Cancer Society . Abstract : A complex karyotype is associated with inferior prognosis in patients with mantle cell lymphoma independent of specific cytogenetic abnormalities, the mantle cell lymphoma International Prognostic Index, and the Ki‐67 proliferative index. Intensive cytarabine‐containing induction therapy does not salvage the inferior survival in patients with a complex karyotype.